Achieving 1 GPa fatigue strength in nanocrystalline 316L steel through recovery annealing. (August 2022) - Renk, O.; Hohenwarter, A.; Gammer, C.; Eckert, J.; Pippan, R.
Abstract: Nanostructured metals offer an improved fatigue limit and high cycle fatigue performance compared to their microcrystalline counterparts. However, even the small cyclic plastic strain amplitudes present at these cyclic loading regimes can induce grain growth, a prerequisite for fatigue crack initiation. Retarding cyclically induced grain growth, for instance by alloying, should thus further improve the fatigue performance. Here, we followed a different strategy and investigate the role of recovery heat treatments, known to shift the onset of plasticity to higher stress levels. Indeed, we observe for the recovered specimens an unprecedented increase of the fatigue limit, reaching for 316L steel values of almost 1 GPa at a stress ratio of R =-1. First experiments further indicate that this strategy could also be used to improve the fatigue limit of conventionally cold worked austenitic structures. Graphical abstract: Image, graphical abstract